Risk of non‐melanoma skin cancer in myasthenia patients treated with azathioprine. (16th December 2013) - Pedersen, E. G.; Pottegård, A.; Hallas, J.; Friis, S.; Hansen, K.; Jensen, P. E. H.; Gaist, D.
<x xml:space="preserve">Abstract</x> Background and purpose The association between use of azathioprine and risk of non‐melanoma skin cancer (NMSC) in patients with myasthenia was evaluated in a nationwide setting. Treatment of autoimmune myasthenia frequently involves long‐term exposure to immunosuppressants, including azathioprine. Use of azathioprine increases the risk of NMSC in organ recipients and probably also in patients with other autoimmune disorders. No previous study has specifically investigated the risk of NMSC in myasthenia patients treated with azathioprine. Methods This is a case–control study based on Danish population‐based registries. Cases were myasthenia patients with a first time diagnosis of NMSC during 2004–2009. Age‐ and sex‐matched controls were selected amongst myasthenia patients with no history of cancer using incidence density sampling. Prior use of azathioprine in cases and controls was assessed through prescription records (1995–2009). Conditional logistic regression was used to calculate odds ratios (OR) with 95% confidence intervals (CI) for skin cancer associated with a high cumulative dose (≥150 g) or long‐term use (≥5 years) of azathioprine, adjusted for confounders. Results Thirty NMSC cases and 360 matched controls were identified. Ever use of azathioprine was associated with a considerably increased risk of NMSC (OR 3.3, 95% CI 1.5–7.3) that was even more apparent in patients with high cumulative dose (OR 4.6, 95% CI 1.7–12.5) or long‐term (OR 4.8; 95% CI 1.7–13.6) use of azathioprine. Conclusion Azathioprine use in patients with myasthenia is associated with an increased risk of NMSC.